2008
DOI: 10.1097/hjh.0b013e3282f624d9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of microalbuminuria in the general population of Seychelles and strong association with diabetes and hypertension independent of renal markers

Abstract: The prevalence of MAU was high in this population, and MAU was strongly associated with several cardiovascular risk factors independently of renal function markers. These findings suggest that MAU could be a useful marker of cardiovascular risk in this population and help identify persons in need of a specific cardiovascular risk management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 42 publications
0
22
2
Order By: Relevance
“…These results are contrary to previous studies which reported significant correlation between microalbuminuria and duration of diabetes [11,20]. While some previous studies did not find any association between duration of diabetes and MA [4,12].…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…These results are contrary to previous studies which reported significant correlation between microalbuminuria and duration of diabetes [11,20]. While some previous studies did not find any association between duration of diabetes and MA [4,12].…”
Section: Discussioncontrasting
confidence: 57%
“…In many African countries, diabetes may go undetected for long periods probably due to less frequent hospital visits and newly diagnosed cases of diabetes may present with wellestablished complications [12]. It has been established that during the first five years of diabetes microalbuminuria is rarely found [20] and early diagnosis of MA may be beneficial in preventing the progression to DN and other overt complications [20]. Interesting, 12 (42.85%) of patients with MA had a duration of diabetes of ≤ 5years, implying that these cases could benefit from screening programme.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are extremely few reports from large-scale studies that examine blood pressure and blood glucose levels at which the risk of microalbuminuria begins to increase. [10][11][12][13] Moreover, no such study has been conducted in Asia. If the purpose of the new health checkup system is to prevent cardiovascular or renal disease, interventions should preferably be made as soon as possible and at an early and appropriate stage.…”
Section: Introductionmentioning
confidence: 99%
“…[17] The formula of Cockcroft and Gault equation was used to calculate estimated glomerular filtration rate (eGFR) [18] . …”
Section: Assessmentmentioning
confidence: 99%